Medium materials for improving frost detection on a resistive sensor - Aguiar, Martim Lima (2022)
Reducing food waste demands improvements in refrigeration systems. Furthermore, the rise of temperatures worldwide demands more capable and efficient refrigeration equipment. One of the problems that affects refrigeration equipment is the accumulation of frost in the heat exchanger that reduces efficiency, and in extreme cases, blocks the air flow. Usually, defrosting is timed for the worst-case scenario, which results in many unnecessary defrosting operations that compromise the efficiency, and temperature stability in the refrigerated environment. This paper presents a low-cost resistive sensor’s reliability case studies, using several materials and configurations.